On a paraconsistentization functor in the category of consequence structures. Issue 3 (2nd July 2016) - de Souza, Edelcio G.; Costa-Leite, Alexandre; Dias, Diogo H. B.
Abstract : This paper is an attempt to solve the following problem: given a logic, how to turn it into a paraconsistent one? In other words, given a logic in which ex falso quodlibet holds, how to convert it into a logic not satisfying this principle? We use a framework provided by category theory in order to define a category of consequence structures. Then, we propose a functor to transform a logic not able to deal with contradictions into a paraconsistent one. Moreover, we study the case of paraconsistentization of propositional classical logic.